Port benchmark - Bouabid, Mohamed Hachem (2014)
This project, through a literature review, analyses the various performance indicators and metrics used by academics and practitioners. Research reveals that there is not a standard practice that has been agreed among ports, international institutions, and academics and expert in the field of maritime ports about what measures should be used and how to calculate them. Many authors analysed port performance indicators and port efficiency, but common conclusions have never been reached and the field remains characterised by a large consistency. Given the lack of clear performance measurement frameworks in the port industry, this paper attempts to remedy to this gap. Bichou’s (2007) work is presented; in contrast with the traditional fragmented methodologies, it conceptualises ports from a logistics and SCM standpoint. The importance of externally generated data was also stressed in this paper (Pallis & Vitsounis, 2008). Another attempt to further improve the port performance measurement practices was designed by the author; it is an adaptation of the Prism performance framework to the seaport industry. This framework has been judged appropriate given the complex stakeholder environment that surrounds the port industry. This paper also presents and analyses a couple of benchmarks performed in practice. The first benchmark is a very interesting initiative by Rankine (2003); it gives industry standards to help ports compare their performance. It has the specificity to be the first project in its kind. The second example is a benchmarking initiative